(untitled) (Global Journal of Human-Social Science, 2020)
Gurudev Rabindranath Tagore realized the need for co-operative for the development of very ordinary village people more than a hundred years ago, but still, there is a lack of consciousness and lack of action both on the part of people and government. The community development projects or programs for rural development in the country got high priority in Independent India after 1947, and till then, it is the areas of the country’s big concern. However, with all attempts of the governmentexperiment and again experiment shows the result of very sloth progress or sometimes assorted picture in agriculture and allied activities, now compel us to evaluate the entire process and step forward to adopt the strategy of the cooperative system to address the problems and to achieve the desired result. In this connection, we seriously need to feel the necessity and appropriateness of Tagore’s thought of cooperative system in various economic and social activities with modification as necessary to re-back the rural life as asset-based, resourceful, self-help, and self-reliant.